2015
DOI: 10.1080/10548408.2014.904259
|View full text |Cite
|
Sign up to set email alerts
|

Using a Choice Experiment (CE) to Value the Attributes of Cruise Tourism

Abstract: Recently, cruise tourism has drawn public interest in the Republic of Korea. In this study, we attempt to analyze people's preferences regarding the attributes of cruise tourism, such as duration, accommodation, services, and cost. Thus, we applied a choice experiment (CE) to measure the marginal willingness to pay (MWTP) for each attribute. The results show that the coefficients of the attributes of onboard activities are positive and statistically significant. MWTPs for increasing the cabin level from an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…For example, this technique was employed to examine tourists' preferences associated with ecotourism development [11,12], tourists' preferences for biodiversity conservation and scenic beauty [13], and tourist preferences for ecotourism development in protected areas [14,15]. Furthermore, some other studies used this approach to evaluate the tourists' preferences for effective attributes associated with tourism resources [16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, this technique was employed to examine tourists' preferences associated with ecotourism development [11,12], tourists' preferences for biodiversity conservation and scenic beauty [13], and tourist preferences for ecotourism development in protected areas [14,15]. Furthermore, some other studies used this approach to evaluate the tourists' preferences for effective attributes associated with tourism resources [16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…The set of attributes and their levels used to create the choice experiment are presented in Table 1. The selection of attributes and the levels for each attribute was based upon research from similar studies [14,21,22], feedback from focus group participants who have visited Jeongseon_gun several times for tourism, and advice from the rural tourism experts to determine the important attributes associated with rural tourism experience. They expressed in general a similar opinion that while staying and enjoying all kinds of tourism resources available in Jeongseon_gun, most of the activities the households are more likely to enjoy would be the local-based festival/show/events as well as exhilarating outdoor adventure.…”
Section: Methodsmentioning
confidence: 99%
“…E. A. Ramoa, Ardigó, & Flores, 2016). Therefore, knowing that this customer is looking for value rather than price (Aaker & McLoughlin, 2010;Lee & Yoo, 2015;Walker & Moscardo, 2014) organizations should consider that positive environmental factors can improve their image vis-à-vis the market and can be interpreted as an added value that will attract consumers (Gössling, Hall, Ekström, Engeset, & Aall, 2012;Lima, Cunha, Moreira, & Porte, 2012;Melissen, 2013;Moriarty, 2012;L. R. de Oliveira, Martins, & Lima, 2010;L.…”
Section: Resultsmentioning
confidence: 99%
“…Hole (2007) discussed and further tested the approaches of estimating confidence intervals for WTP. Lee and Yoo (2015) used the choice experiment approach to research the marginal WTP for increasing the attributes of cruise facilities (e.g. cruise duration, accommodation, services and cost) and found that the marginal WTP is substantially more influenced by cruise on-board facilities rather than by port visits.…”
Section: Theory Backgroundmentioning
confidence: 99%
“…Although consumption behaviours of cruise tourists has received attention (Brida et al, 2014;Lee and Yoo, 2015), little is known about the determinants of cruise WTP and the differences of cruise WTP in different market segments. No prior studies have considered explicitly these perspectives.…”
Section: Introductionmentioning
confidence: 99%